Normalization of Sentinel 2 data over tropical forests to nadir BRDF adjusted reflectance - Pierre Ploton; Gaëlle Viennois; Florian de Boissieu; Erik Lindquist; Jean-Baptiste Féret; Daniel Wiell; Hervé Poilvé; Pierre Couteron; Raphaël Pélissier; Nicolas Barbier (Remote Sensing of Environment, 2026)

Logging impact on giant herb density and reproductive strategies in central African moist forests - Juliette Picard; Victoire Jessica Ngambe; Olivier J. Hardy; Chauvelin Douh; Vivien Rossi; Pierre Couteron; Eric Forni; Jean-Joël Loumeto; Belvina Chardène Mabengo; Gilbert Nsongola; Yorick van Hoef; Maxime Réjou-Méchain (Forest Ecology and Management, 2026)

The biogeography of Gabonese savannas: Evidence from termite community richness and composition - Fidèle Evouna Ondo; Kathryn J. Jeffery; Robin Whytock; Katharine A. Abernethy; Pierre Couteron; Paul Eggleton; Claire Griffin; Nicolas J. Ostle; Aurelie‐Flore Koumba Pambo; Alfred Ngomanda; Josué Edzang Ndong; Catherine L. Parr (Journal of Biogeography, 2023)
Aim The mosaic of savannas that persists in the forest‐dominant Congo Basin is thought to be palaeoclimatic relics, but past biogeographical processes that have formed and maintained these systems are poorly understood. Here, we explored the post‐Pleistocene biogeography of Gabon's savannas using termites as biological indicators to understand historical and mechanistic factors influencing present‐day termite communities in the country's extant savannas. Location Gabon, Central Africa. Taxon Blattodea: Termitoidae. Methods Using standardised transect methods, we sampled termite communities in four disjunct modern savanna areas of Gabon: the centre (Lopé), the southeast (Batéké) and the south (Mayombe North and South). Termites at Lopé were collected in three habitats (annually burned savannas, savannas with a depressed fire regime and forest). We used DNA barcoding of the COII region to identify termite species and compared abundance, species richness and community composition across areas and habitats. Results Community composition differed greatly between Lopé and both Batéké and Mayombe savannas with Lopé being exceptionally depauperate and lacking characteristic savanna species. Within Lopé, termite abundance and diversity was highest in forests and lowest in annually burned savannas, with a gradual change in species composition across the forest–savanna gradient associated with fire history. Main Conclusions The absence of savanna typical species in Lopé savannas challenges current assumptions that these savannas were linked to the south/southeastern savannas during the Pleistocene and suggests a different evolutionary history. Lopé savannas may instead have opened as an isolated grassland and never have been contiguous with neighbouring savannas, or were isolated soon after forest expansion began and have now lost savanna‐typical species. Furthermore, the patterns of termite community composition in fire suppressed savannas support a hypothesis of rapid change driven by fire frequency where either fire suppression or infrequent burning over 23 years has meant savannas have become ecologically much more forest‐like.

Upscaling Forest Biomass from Field to Satellite Measurements: Sources of Errors and Ways to Reduce Them - Maxime Réjou-Méchain; Nicolas Barbier; Pierre Couteron; Pierre Ploton; Grégoire Vincent; Martin Herold; Stéphane Mermoz; Sassan Saatchi; Jérôme Chave; Florian de Boissieu; Jean-Baptiste Féret; Stéphane Momo Takoudjou; et al. (Surveys in Geophysics, 2019)

Estimation of Above Ground Biomass Using Texture Metrics Derived from IRS Cartosat-1 Panchromatic Data in Evergreen Forests of Western Ghats, India - R. Suraj Reddy; G. Rajashekar; C. S. Jha; V. K. Dadhwal; Raphel Pelissier; Pierre Couteron (Journal of the Indian Society of Remote Sensing, 2017)

Contrasted allometries between stem diameter, crown area, and tree height in five tropical biogeographic areas - Elodie Blanchard; Philippe Birnbaum; Thomas Ibanez; Thomas Boutreux; Cécile Antin; Pierre Ploton; Grégoire Vincent; Robin Pouteau; Hervé Vandrot; Vanessa Hequet; Nicolas Barbier; Vincent Droissart; et al. (Trees, 2016)

How do habitat filtering and niche conservatism affect community composition at different taxonomic resolutions? - François Munoz; B. R. Ramesh; Pierre Couteron (Ecology, 2014)
Understanding how local species assembly depends on the regional biogeographic and environmental context is a challenging task in community ecology. In spatially implicit neutral models, a single immigration parameter, I ( k ), represents the flux of immigrants from a regional pool that compete with local offspring for establishment in communities. This flux counterbalances the effect of local stochastic extinctions to maintain local species diversity. If some species within the regional pool are not adapted to the local environment (habitat filtering), the migrant flux is reduced beyond that of the neutral model, such that habitat filtering influences the value of I ( k ) in non‐neutral situations. Here, we propose a novel model in which immigrants from the regional pool are filtered according to their habitat preferences and the local environment, while taxa potentially retain habitat preferences from their ancestors (niche conservatism). Using both analytical reasoning and simulations, we demonstrate that I ( k ) is expected to be constant when estimated based on the community composition at several taxonomic levels, not only under neutral assumptions, but also when habitat filtering occurs, unless there is substantial niche conservatism. In the latter case, I ( k ) is expected to decrease when estimated based on the composition at species to genus and family levels, thus allowing a signature of niche conservatism to be detected by simply comparing I ( k ) estimates across taxonomic levels. We applied this approach to three rain forest data sets from South India and Central America and found no significant signature of niche conservatism when I ( k ) was compared across taxonomic levels, except at the family level in South India. We further observed more limited immigration in South Indian forests, supporting the hypothesis of a greater impact of habitat filtering and heterogeneity there than in Central America. Our results highlight the relevance of studying variations of I ( k ) in space and across taxonomic levels to test hypotheses about the ecological and evolutionary drivers of biodiversity patterns.

Crown allometries are less responsive than stem allometry to tree size and habitat variations in an Indian monsoon forest - Cécile Antin; Raphaël Pélissier; Grégoire Vincent; Pierre Couteron (Trees, 2013)

Phylogenetic turnover in tropical tree communities: impact of environmental filtering, biogeography and mesoclimatic niche conservatism - Olivier J. Hardy; Pierre Couteron; François Munoz; B. R. Ramesh; Raphaël Pélissier (Global Ecology and Biogeography, 2012)
Aim We addressed the roles of environmental filtering, historical biogeography and evolutionary niche conservatism on the phylogenetic structure of tropical tree communities with the following questions. (1) What is the impact of mesoclimatic gradients and dispersal limitation on phylogenetic turnover and species turnover? (2) How does phylogenetic turnover between continents compare in intensity with the turnover driven by climatic gradients at a regional scale? (3) Are independent phylogenetic reconstructions of the mesoclimatic niche of clades congruent between continents? Location Panama Canal Watershed and Western Ghats (India), two anciently divergent biogeographic contexts but with comparable rainfall gradients. Methods Using floristic data for 50 1‐ha plots in each region, independent measures of phylogenetic turnover (Π ST ) and species turnover (Jaccard) between plots were regressed on geographic and ecological distances. Mesoclimatic niches were reconstructed for each node of the phylogeny and compared between the two continents. Results (1) The phylogenetic turnover within each region is best explained by mesoclimatic differences (environmental filtering), while species turnover depends both on mesoclimatic differences and geographic distances (dispersal limitation). (2) The phylogenetic turnover between continents (Π ST = 0.009) is comparable to that caused by mesoclimatic gradients within regions (Π ST = 0.010) and both effects seem cumulative. (3) Independent phylogenetic reconstructions of the mesoclimatic niches were strongly correlated between the two continents ( r = 0.61), despite the absence of shared species. Main conclusions Our results demonstrate a world‐wide deep phylogenetic signal for mesoclimatic niche within a biome, indicating that positive phylogenetic turnover at a regional scale reflects environmental filtering in plant communities.

The variation of apparent crown size and canopy heterogeneity across lowland Amazonian forests - Nicolas Barbier; Pierre Couteron; Christophe Proisy; Yadvinder Malhi; Jean‐Philippe Gastellu‐Etchegorry (Global Ecology and Biogeography, 2010)
Aim The size structure of a forest canopy is an important descriptor of the forest environment that may yield information on forest biomass and ecology. However, its variability at regional scales is poorly described or understood because of the still prohibitive cost of very high‐resolution imagery as well as the lack of an appropriate methodology. We here employ a novel approach to describe and map the canopy structure of tropical forests. Location Amazonia. Methods We apply Fourier transform textural ordination (FOTO) techniques to subsamples of very high‐resolution satellite imagery freely available through virtual globe software (e.g. Google Earth®) to determine two key structural variables: apparent mean crown size and heterogeneity in crown size. A similar approach is used with artificial forest canopy images generated by the light interaction model (discrete anisotropic radiative transfer, DART) using three‐dimensional stand models. The effects of sun and viewing angles are explored on both model and real data. Results It is shown that in the case of canopies dominated by a modal size class our approach can predict mean canopy size to an accuracy of 5%. In Amazonia, we could evidence a clear macrostructure, despite considerable local variability. Apparent crown size indeed consistently increases from about 14 m in wet north‐west Amazonia to more than 17 m for areas of intermediate dry season length (1–3 months) in south and east Amazonia, before decreasing again towards the ecotone with the Cerrado savanna biome. This general trend reflects the known variation of other forest physiognomic properties (height) reported for South America and Africa. Some regions show significantly greater canopy heterogeneity, a feature that may be related to substratum, perturbation rate and/or forest turnover rate. Main conclusions Our results demonstrate the feasibility and interest of large‐scale assessment of rain forest canopy structure.

The global biogeography of semi‐arid periodic vegetation patterns - Vincent Deblauwe; Nicolas Barbier; Pierre Couteron; Olivier Lejeune; Jan Bogaert (Global Ecology and Biogeography, 2008)
Aim Vegetation exhibiting landscape‐scale regular spatial patterns has been reported for arid and semi‐arid areas world‐wide. Recent theories state that such structures are bound to low‐productivity environments and result from a self‐organization process. Our objective was to test this relationship between periodic pattern occurrence and environmental factors at a global scale and to parametrize a predictive distribution model. Location Arid and semi‐arid areas world‐wide. Methods We trained an empirical predictive model (Maxent) for the occurrence of periodic vegetation patterns, based on environmental predictors and known occurrences verified on Landsat satellite images. Results This model allowed us to discover previously unreported pattern locations, and to report the first ever examples of spotted patterns in natural systems. Relationships to the main environmental drivers are discussed. Main conclusions These results confirm that periodic patterned vegetations are ubiquitous at the interface between arid and semi‐arid regions. Self‐organized patterning appears therefore to be a biome‐scale response to environmental conditions, including soil and topography. The set of correlations between vegetation patterns and their environmental conditions presented in this study will need to be reproduced in future modelling attempts.

ANALYZING OR EXPLAINING BETA DIVERSITY? COMMENT - Raphaël Pélissier; Pierre Couteron; Stéphane Dray (Ecology, 2008)

Using spectral analysis to confront distributions of individual species with an overall periodic pattern in semi-arid vegetation - Pierre Couteron (Plant Ecology, 2001)

Woody vegetation spatial patterns in a semi-arid savanna of Burkina Faso, West Africa - Pierre Couteron; Kouami Kokou (Plant Ecology, 1997)